(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Ancient University plays a key role in spreading the Buddhism beyond the borders of the India.Six major universities served as the foundation for the development and dissemination of Buddhist knowledge in ancient India: Nalanda, Vikramashila, Odantapuri, Jagaddala, Somapura, and Valabhi. Among these, Nalanda stands out as a pioneering institution, established around 500 years before the founding of the University of Bologna, often regarded as the world’s oldest university.